2021
DOI: 10.1073/pnas.2012898118
|View full text |Cite
|
Sign up to set email alerts
|

CMT2N-causing aminoacylation domain mutants enable Nrp1 interaction with AlaRS

Abstract: Through dominant mutations, aminoacyl-tRNA synthetases constitute the largest protein family linked to Charcot-Marie-Tooth disease (CMT). An example is CMT subtype 2N (CMT2N), caused by individual mutations spread out in AlaRS, including three in the aminoacylation domain, thereby suggesting a role for a tRNA-charging defect. However, here we found that two are aminoacylation defective but that the most widely distributed R329H is normal as a purified protein in vitro and in unfractionated patient cell samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…Although there has been debate (32, 51) as to whether AARS1 functions as a dimer or a monomer, the results of our study demonstrate that it likely functions as a dimer in vivo , which is a requirement for a dominant-negative mechanism of disease. Previous studies using purified AARS1 protein for in vitro enzymatic assays determined that the C-terminal dimerization domain (beginning at G757) is dispensable for aminoacylation (51).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although there has been debate (32, 51) as to whether AARS1 functions as a dimer or a monomer, the results of our study demonstrate that it likely functions as a dimer in vivo , which is a requirement for a dominant-negative mechanism of disease. Previous studies using purified AARS1 protein for in vitro enzymatic assays determined that the C-terminal dimerization domain (beginning at G757) is dispensable for aminoacylation (51).…”
Section: Discussionmentioning
confidence: 65%
“…While the data presented here strongly argue in favor of a dominant-negative effect, it is possible that a dominant-negative and neomorphic gain-of-function effects work in concert to exacerbate neuronal pathology. A recent study showed that the pathogenic AARS1 variants N71Y, G102R, and R329H each cause a conformational change that enables binding to Neuropilin-1 (32), a widely expressed receptor that modulates a variety of signalling pathways and that is critical for neurovascular development (57). Although such an interaction might compound the damage in patient neurons, our yeast model demonstrates that a neuron-specific (or mammalian-specific) interaction is not required for pathogenic AARS1 alleles to exert dominant effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The necessity of GlyRS binding NRP1 for the disease mechanism leading to neuropathy is called into question by the failure of NRP1 to bind ΔETAQ, a four amino acid internal deletion in GlyRS that causes a severe, early onset neuropathy in both mice and humans ( Morelli et al, 2019 ). Nonetheless, several other neuropathy-associated mutant GlyRS proteins bind NRP1, as do CMT2N-associated alleles of AARS , suggesting that it may in some way be contributing to the disease severity and pathogenesis ( He et al, 2015 ; Sun et al, 2021 ). This also suggests that small molecules to block this interaction or antibodies to clear mutant GlyRS proteins could be therapeutic strategies.…”
Section: Cellular and Biochemical Mechanisms Suggest Therapeutic Strategiesmentioning
confidence: 99%
“…Dominant mutations in several genes encoding tRNA aminoacyl synthetases are associated with Charcot-Marie-Tooth (CMT) disease and characterization of the corresponding mutants has demonstrated that aminoacylation activity is frequently not impaired. Instead, the mutations induce an alternative open conformation of the enzyme, which exposes a surface for new protein interactions (He et al, 2011;Blocquel et al, 2017;Bervoets et al, 2019;Blocquel et al, 2019;Sun et al, 2021), indicating a gain-of-function mechanism. In the case of leukodystrophies caused by bi-allelic mutations in genes encoding aaRS1, caused by hypomorphic mutations, further studies are required to determine if there is an underlying mechanism that involves translation deregulation and/or shares features with POLR3-HLD.…”
Section: Function Of Pol III Transcripts and Role In Polr3-related Disorders Expression And Functions Of Trnasmentioning
confidence: 99%